2017
DOI: 10.1101/178715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of dispersal syndrome and its corresponding metabolomic changes

Abstract: 1Dispersal is one of the strategies for organisms to deal with climate change and habitat 2 degradation. Consequently, the effects of dispersal evolution on behavioural and life-history the dispersal-selected populations had significantly greater locomotor activity, exploratory 7 tendency and aggression but similar values of body size, fecundity and longevity. Untargeted 8 metabolomics using NMR spectroscopy suggested that the selected flies had elevated levels of 9 cellular respiration and octopamine, but les… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 111 publications
(101 reference statements)
4
12
0
Order By: Relevance
“…As expected from previous studies (Tung, Mishra, Gogna, et al, 2018; Tung, Mishra, Shreenidhi, et al, 2018), the minimum adequate model (MAM) for dispersal propensity revealed a significant main effect of dispersal selection ( t = −5.99, p < 10 –5 ), with VB individuals being more dispersive than VBC individuals. The effects of both sex and dispersal selection × sex interaction were found to be non‐significant at various stages of model selection (Text S2.1), thereby excluding them from the MAM.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As expected from previous studies (Tung, Mishra, Gogna, et al, 2018; Tung, Mishra, Shreenidhi, et al, 2018), the minimum adequate model (MAM) for dispersal propensity revealed a significant main effect of dispersal selection ( t = −5.99, p < 10 –5 ), with VB individuals being more dispersive than VBC individuals. The effects of both sex and dispersal selection × sex interaction were found to be non‐significant at various stages of model selection (Text S2.1), thereby excluding them from the MAM.…”
Section: Resultssupporting
confidence: 80%
“…VB 4 undergoes selection for higher dispersal every generation, while VBC 4 serves as its corresponding control (Tung, Mishra, Shreenidhi, et al, 2018). As a result of this selection, VB flies have evolved a higher dispersal propensity (see Section 2.5 below) and locomotor activity than the corresponding VBC flies (Tung, Mishra, Gogna, et al, 2018; Tung, Mishra, Shreenidhi, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…1, see also Supplementary Figure 1 for fecundity at 24h). Our findings in our one generation experiment are here similar to those of Tung et al (2018) in Drosophila melanogaster after several generations of selection for dispersal. They suggested that this stability of body size and fecundity despite the constitutive and induced costs of dispersal was offset by a shorter lifespan; our experiment was not designed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…Metabolic profile changes in response to stress exposure, and their (putative) functional roles, have been extensively documented, especially in arthropods (Bundy et al, 2008; Steinberg, 2012; Teets and Denlinger, 2013). In contrast, metabolite differences between dispersers and residents even in interaction with the environment- are surprisingly understudied, compared to other phenotypic differences (Cote et al, 2017; Ronce and Clobert, 2012; but see Tung et al, 2018; Van Petegem et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…This finding is consistent with the theory that individuals of a population that forage on the same resources can differ on the genetic level in how these resources are metabolized and that these differences influence their movement behavior [137]. In Drosophila that were artificially selected for increased dispersal, higher amounts of octopamine and serotonin were detected [161]. These neurotransmitters are associated with an elevated exploratory behavior in animals, while octopamine is also known to be important when energy reserves have to be mobilized [162,163].…”
Section: Using Metabolomics and Gene-editing To Find And Validate Keysupporting
confidence: 86%